BASES OF MILITARY-SOCIAL WORK IN THE UKRAINE ARMED FORCES AND THE WORLD LEADING COUNTRIES ARMY (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article discusses the content of the military-social work of the Ukraine Armed Forces as a moral and psychological support component. The functions, tasks and content of military-social work are revealed. The understanding of the military-social work content has been supplemented and expanded. A comparative analysis of the social workers and volunteer activities in the Ukraine Armed Forces and the foreign countries armies was carried out.The specialization of the social worker was marked as a complex of social-legal, economic and vigorous calls, conducted by the state, government bodies, commanders and headquarters of all regions, and all of them, member of the group of services. The military social work main tasks are highlighted: protection of social norms and guarantees of military personnel in accordance with existing legislation; implementation of measures to reduce the social tension of military collectives; research of social processes in military collectives; creation of prerequisites for the formation and maintenance of high combat activity of personnel; adaptation of military personnel to changing conditions, work with families of military personnel. The fact that in the Armed Forces of Ukraine military-social work is primarily informational, advisory in nature, rather than the practical implementation of measures to ensure the social protection of the state's military personnel, has been ascertained.
Keywords: social protection, military-social work, post-traumatic stress disorder, Armed Forces of Ukraine, Canadian Armed Forces, US Armed Forces, mental health, volunteer public organizations.